Employment activity of the older generation – does the European Year of Active Ageing and Solidarity between Generations 2012 promote it successfully - Urbaniak, Bogusława (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
This article compares the aims and the methodology of activities connected with the national "celebration" of the European Year of Active Aging and Solidarity between Generations 2012 with the aims of the European Year 2012 and of the European Employment Strategy in the context of the priorities of the Europe 2020 strategy. The activities emphasise the use of the open method of coordination that involves a dialogue between the European Commission, national governments, trade unions, employers' organisations and other European institutions, such as the European Economic and Social Committee. The article raises questions about the degree to which the activities related to the Polish National Action Plan for the European Year of Active Aging and Solidarity between Generations 2012 are capable of improving the values of the indicators used to monitor the fulfillment of the goals. The article critically evaluates the main activities, pointing to the weaknesses of social dialogue in Poland that falls short of the realities because of its centralisation. The centralised approach has caused that the government side is the major player in the dialogue that marginalises the collective voice of trade unions on issues important for the planned extension of the retirement age. In some countries, such as Norway, the bilateral dialogue between social partners is central to high employment activity of older people. As far as employers are concerned, they tend to develop adaptation strategies to the general aging of societies.